Membrane Selection for Electrochemical Treatment of Septage - Talekar, Guruprasad V.; Mutnuri, Srikanth (Frontiers in Energy Research, 2020)
The development of economically feasible and efficient decentralized onsite treatment of septic tank water or blackwater is the need of the hour. In recent years, Electrochemical oxidation (EO) has been proven to be an efficient alternative treatment technology for use in small-scale, onsite wastewater treatment operations. Recently, the electrochemical treatment of wastewater in membrane divided cells has been reported to be of superior efficiency with regards to chemical oxygen demand (COD) removal while producing fewer disinfection by-products. In this study, a reduction of all the major wastewater defining parameter in both the anode and cathode chambers of an Anionic exchange membrane divided electrochemical reactor (AEM-ECR) and a Cationic exchange membrane divided electrochemical reactor (CEM-ECR) were obtained after the electrolysis of real septage and septage that had passed a vertical flow constructed wetland (VFCW), respectively. The results of these batch electrolysis experiments in AEM-ECR and CEM-ECR using septage as feed concluded that among the two studied membranes, AEM usage in ECR is optimal. The reduction in COD, Total Organic Carbon (TOC), and Total ortho-phosphate (TP) after electrolysis in AEM based ECR was found to be double that achieved in CEM-ECR. The charge supplied and power required were 7794 ± 10 coulombs L−1 and 48 ± 6.7 Wh L−1. Further, the results of the batch electrolysis experiments in AEM-ECR with VFCW treated septage as feed concluded that the optimum feed to the AEM-ECR is VFCW treated septage since the charge and power requirement for treatment of VFCW treated septage is 42.5 and 35% lower, respectively, to that required for septage for similar percentage reductions in COD, TOC, and TP. The charge supplied and power required was 4482 ± 846 coulombs L−1 and 31 ± 1.6 Wh L−1. Finally, the continuous flow experiments ACAEM and CAAEM concluded that, regarding the double-chambered membrane ECR, a feed flow mode from anode to cathode results in maximum reduction in COD, TOC, TP, and coliforms in a double-chambered membraned ECR. The power required for treatment was 21.2 Kwh/m3.